2017
DOI: 10.1016/j.conb.2017.07.008
|View full text |Cite
|
Sign up to set email alerts
|

What can neuronal populations tell us about cognition?

Abstract: Nowadays, it is possible to record the activity of hundreds of cells at the same time in behaving animals. However, these data are often treated and analyzed as if they consisted of many independently recorded neurons. How can neuronal populations be uniquely used to learn about cognition? We describe recent work that shows that populations of simultaneously recorded neurons are fundamental to understand the basis of decision-making, including processes such as ongoing deliberations and decision confidence, wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 98 publications
0
12
0
Order By: Relevance
“…Identifying the statistical features of neuronal population responses that affect the amount of encoded information and be-havioral performance is critical for understanding neuronal population coding (Arandia-Romero et al, 2017;Panzeri et al, 2017). Changes in network states, such as global modulations of activity (Harris and Thiele, 2011;Luczak et al, 2013;Gutnisky et al, 2017), as well as changes in correlated noise among neurons, have been shown to constrain the amount of information encoded by neuronal populations (Zohary et al, 1994;Ecker et al, 2014;Lin et al, 2015;Schölvinck et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Identifying the statistical features of neuronal population responses that affect the amount of encoded information and be-havioral performance is critical for understanding neuronal population coding (Arandia-Romero et al, 2017;Panzeri et al, 2017). Changes in network states, such as global modulations of activity (Harris and Thiele, 2011;Luczak et al, 2013;Gutnisky et al, 2017), as well as changes in correlated noise among neurons, have been shown to constrain the amount of information encoded by neuronal populations (Zohary et al, 1994;Ecker et al, 2014;Lin et al, 2015;Schölvinck et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Identifying the statistical features of neuronal population responses that affect the amount of encoded information and behavioral performance is critical for understanding neuronal population coding (Arandia-Romero et al 2017;Panzeri et al 2017). The modulation in mean firing rate of individual neurons with respect to a stimulus parameter is a statistical feature that has been typically taken as evidence for encoding information about that stimulus (Hubel and Wiesel 1959;Mountcastle et al 1967).…”
Section: Introductionmentioning
confidence: 99%
“…However, the aspects of neuronal responses that most directly affect the amount of encoded information are not clear, since experimental designs often do not allow control over other statistical features that could potentially be involved. Furthermore, it is unknown whether the same features of population responses that affect the amount of encoded information also impact behavioral performance (Arandia-Romero et al 2017;Panzeri et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For encoding, generalized linear models (GLMs), a generalization of multiple linear regression, regress neuronal activity against behavioral variables to determine the set of variables that explain more neuronal activity (Aljadeff et al, 2016;Nogueira et al, 2017). Decoding techniques, typically linear classifiers (Arandia-Romero, Nogueira, Mochol, & Moreno-Bote, 2017;Quian Quiroga & Panzeri, 2009), as well as more recent artificial neural networks (ANNs; Paninski & Cunningham, 2018) are used to predict, trial-by-trial, values of behavioral variables from neuronal activity, either using single neuronal activity or the individual activity of large neuronal populations recorded from multielectrode-arrays or Ca 2+ imaging. These methods are supervised machine learning tools because both behavioral and neuronal variables are preselected and labeled.…”
Section: Statistical Tools For Understanding Datamentioning
confidence: 99%